APLICAÇÕES DE FUNGICIDAS EM DIFERENTES ESTÁDIOS DA CULTURA DA SOJA EM DOIS LOCAIS - Freitas, José de (2012)
The main diseases occurring in soybean (Glycine max) in Brazil have a great damage potential, requiring additional expenses to control through measures available today, highlighting the fungicides spray. The objective of this study was to evaluate the effect of fungicides spray at different growth stages of soybean, cultivar CD 206, and verify the relation between the severity of powdery mildew (Erysiphe diffusa) and of asian soybean rust (Phakopsora pachyrhizi), on yield components. Two experiments were conducted on field one in Arapoti (experiment I) and another in Ponta Grossa (experiment II) in the region of Campos Gerais, Paraná. In both local the fungicide was sprayed trifloxystrobin + cyproconazole, in a rate of 56,4 + 24,0 mL a. i. ha-1, was added ajduvante methyl ester of soybean oil in a rate of 360,0 mL a. i. ha-1. The experimental design was randomized blocks with four replications. The treatments in a total of ten, were composed of fungicides spray in different numbers and growth stages: Experiment I, 1. Control (no spray); 2. R5.2; 3. R4 + R5.2; 4. R2 + R4 + R5.2; 5. V9 + R2 + R4 + R5.2; 6. V6 + V9 + R2 + R4 + R5.2; 7. V6 + V9 + R2 + R4; 8. V6 + V9 + R2; 9. V6 + V9 and 10. V6. Experiment II, 1. Control (no spray); 2. R5.1; 3. R3 + R5.1; 4. R1 + R3 + R5.1; 5. V8 + R1 + R3 + R5.1; 6. V5 + V8 + R1 +R3 + R5.1, 7. V5 + V8 + R1 + R3; 8. V5 + V8 + R1; 9. V5 + V8 and 10. V5. The treatments were composed in order to generate and compare different percentages of severity of powdery mildew and asian soybean rust obtained by the period of protection or exposure to these diseases. The severity of powdery mildew was evaluated experiment I growth stages R2, R4, R5.3 and R5.5 and in experiment II in R1, R3, R5.2, R5.3 and R5.5. The severity of asian soybean rust was evaluated experiment I in growth at stages R5.3, R5.4, R6 and R7.1, and in experiment II R5.1, R5.2, R5.3, R5.5 and R6. With the data of severity it was calculated the area under the disease progress curve. Were also evaluated defoliation, yield and their components (number of pods per plant, number of grains per plant, grain weight per plant and thousand grain weight). Powdery mildew showed low severity. The asian soybean rust was the disease predominant in high severity, with high damage potential. The fungicides spray reduced disease severity and there was a negative linear relationship with the yield. Long periods without protection of plants allowed rapid reinfection of powdery mildew and spray erradicativas resulted in low efficiency of control powdery mildew and asian soybean rust. The fungicides spray between growth stages R1 to R5.2 promoted protection since the beginning of the epidemic and residual effect, que resulted in less severity, less defoliation, increased grain yield and higher yield.